Key Informants Perspectives on Education Success, Supports, and Barriers in Nunavut Education - Sallaffie, Moriah; Penney, Jessica; Cherba, Maria; Healey Akearok, Gwen K.; Ratel, Jean-Luc (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2022)
In Nunavut, data for 2012–2014 shows a high school graduation rate of 34%. Little has been published about the causes of secondary students’ absenteeism and the methods for attracting students back to school. This study explored the barriers and supports to education success from the perspectives of school staff, students, and parents. Interviews and sharing circles were conducted with 141 participants in six communities. The results revealed barriers and supports in relation to the learning environment, staffing issues, and overarching system. Participants identified specific recommendations that can inform future policy and programming to improve attendance and graduation rates in Nunavut schools.